(untitled) (Computer systems and information technologies, 2021)
The paper presents a method for the detection of anomalies in waste-free production audit data based on the neural network model of Gauss-Bernoulli of the forward only restricted Cauchy machine (FORCM). The purpose of the work is to increase the efficiency of audit data analysis of waste-free production on the basis of the neural network model of anomalies detection without the use of the marked data that simplifies audit. To achieve this goal, the following tasks have been set and solved: offered model of generalized multiple transformations of audit data in the form of a two-layer neural network. Cauchy offered neural network model of Gauss-Bernoulli of the forward only restricted Cauchy machine possesses a heteroassociative memory; works real data; has no restrictions for storage capacity; provide high accuracy of detection of anomalies; uses Cauchy’s distribution that increases the speed of convergence of a method of parametrical identification. To increase the speed of Gauss-Bernoulli parametric identification of a forward only restricted Cauchy machine, a parametric identification algorithm was developed to be implemented on a GPU using CUDA technology. The offered algorithm allows increasing training speed by approximately proportional to the product of numbers of neurons in the hidden layer and power of a training set. The experiments confirmed the operability of the developed software and allow to recommend it for use in practice in a subsystem of the automated analysis of DSS of audit for detection of anomalies.